2016
DOI: 10.1016/j.jad.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

The course of major depressive disorder from childhood to young adulthood: Recovery and recurrence in a longitudinal observational study

Abstract: Background The episodic nature of major depressive disorder (MDD) in clinically referred adults has been well-characterized, particularly by the NIMH Collaborative Depression Study. Previous work has established that MDD also is episodic prior to adulthood, but no study has yet provided comprehensive information on the actual course of MDD in clinically referred juveniles. Thus, the present investigation sought to characterize recovery, recurrence, and their predictors across multiple episodes of MDD in initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 49 publications
(81 reference statements)
4
73
0
2
Order By: Relevance
“…Based on previous research, we expected the number of previous episodes and childhood maltreatment to be identified as predictors as well (Berwian et al., ; Hardeveld et al., ; Kovacs et al., ; Nanni et al., ). However, our selection methods did not identify these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous research, we expected the number of previous episodes and childhood maltreatment to be identified as predictors as well (Berwian et al., ; Hardeveld et al., ; Kovacs et al., ; Nanni et al., ). However, our selection methods did not identify these variables.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, evidence is inconclusive for several predictors, including stressful life events, a family history of MDD, severity of the depressive episode, and comorbidity (e.g., dysthymia and personality pathology, Burcusa & Iacono, ; Hardeveld et al., ; Hardeveld, Spijker, De Graaf, Nolen, & Beekman, ). Only a few predictors have been repeatedly found to relate to an unfavorable long‐term course of MDD, namely the number of previous episodes, residual symptoms, and childhood maltreatment (Berwian, Walter, Seifritz, & Huys, ; Hardeveld, Spijker, De Graaf, Nolen, & Beekman, ; Kovacs, Obrosky, & George, ; Nanni, Uher, & Danese, ). Second, several studies have shown that the risk of recurrence of MDD depends on the combination of multiple predictors each having a small prognostic effect (van Loo et al., ; Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Unipolar depression is characterized as a recurrent disease [36]. Phases with mild to severe symptoms (episodes) alternate with phases without, or with only minimal, symptoms (remission) [37,38].…”
Section: Model Structurementioning
confidence: 99%
“…Consistent with previous research (Barlow, 1991;Heller, Nitschke, Etienne, & Miller, 1997;Nitschke, Heller, Palmieri, & Miller, 1999;Watson, 2005), we defined anxious apprehension as excessive worry for the future and verbal rumination about negative expectations, reflected in generalized anxiety disorder (GAD), obsessive compulsive disorder (OCD), or separation anxiety disorder (SAD). We focused on COD, given its strong association with restingstate prefrontal EEG activity (Shankman & Klein, 2003) and because individuals with COD are at very high risk for recurrent depression and lifetime anxiety disorders (Kovacs, Obrosky, & George, 2016;Maser & Cloninger, 1990).…”
mentioning
confidence: 99%